Emergence of a subordinate construction in a sign language: Intonation ploughs the field for morphosyntax - Svetlana Dachkovsky (Glossa, 2022)
A central question in historical linguistics is how subordination emerges. Many linguists have hypothesized that diachronically subordinate constructions start off with intonational signals, and that these precede morphosyntactic markers of subordination (Givón 2012; Mithun 2009 inter alia). Contemporary spoken languages cannot provide a testing ground for this hypothesis because all of them have fully grammaticalized subordinate constructions. However, a young sign language, such as Israeli Sign Language (ISL), is perfectly suited for this purpose (Meir and Sandler 2008). In ISL, relative clauses are usually marked by squinted eyes and a forward head position, which have been shown to perform the functions of intonation (Sandler 1999; Dachkovsky, Healy and Sandler 2013), as well as by a manual demonstrative form appearing at the relative clause boundary.Yet, consistent marking of relative clauses in the language is characteristic of the younger signers’ but not of the older signers’ language. This suggests that relative clause marking developed over time in the language, which leads us to ask how it emerged and developed. The present study tracks the emergence of the relative clause (RC) construction by investigating changes in intonational and morphosyntactic signals across three generations of ISL signers. The study demonstrates that these signals begin as pragmatic or, more specifically, as information structuring devices, and are transformed by a grammaticalization process into RC markers. Furthermore, we show that intonational cues in the newly emerging RCs pave the way for a morphosyntactic marker.